Lower and Upper Gastrointestinal Symptoms Differ Between Individuals With Irritable Bowel Syndrome With Constipation or Chronic Idiopathic Constipation - Shah, Eric D (J Neurogastroenterol Motil, 2018)
BACKGROUND/AIMS: We evaluated the distribution of lower and upper gastrointestinal (GI) symptoms among individuals with irritable bowel syndrome with constipation (IBS-C) and chronic idiopathic constipation (CIC) in a nationwide survey. METHODS: Individuals (≥ 18 years of age) were identified from a nationwide sample of > 70 000 United States adults. Participants completed the National Institutes of Health GI Patient Reported Outcomes Measurement Information System (NIH GI-PROMIS) questionnaire. Symptom frequency and intensity in the prior 7 days were assessed using validated PROMIS scores. Odds ratios (OR) with 95% confidence intervals (CI) were calculated to compare symptom prevalence in IBS-C vs CIC, and one-way ANOVA was used to assess differences in PROMIS scores. Regression analysis was performed to adjust for demographic variables. RESULTS: Nine hundred and seventy adults met eligibility criteria (275 with IBS-C, 734 with CIC). Demographics were similar among groups except for education, marital and employment status, and income. Adjusting for demographic differences, GI-PROMIS scores of global GI symptoms were higher in IBS-C (251.1; 95% CI, 230.0–273.1) compared to CIC (177.8; 95% CI 167.2–188.4) (P < 0.001). Abdominal pain was more prevalent (OR, 4.3; 95% CI, 2.9–6.6) and more severe (P = 0.007) in IBS-C. Constipation was more severe in IBS-C (P = 0.011). Incontinence was more common (OR, 2.9; 95% CI, 1.3–6.3) but just as severe (P = 0.389) in IBS-C versus CIC. Regarding upper GI symptoms, the prevalence of dysphagia, heartburn, and nausea were similar. However, IBS-C individuals had more severe heartburn (P = 0.001). CONCLUSION: GI symptoms are generally more severe in IBS-C compared to CIC, however abdominal pain, bloating, and upper GI symptoms still commonly occur in CIC.